Estimating Atherosclerosis Cardiovascular Disease Risk of 10-year with the Systemic Coronary Risk Estimation Method and Statin Use Recommendation - Nurmainah - Nurmainah; Syarifah N.Y.R.S Asseggaf (Universitas Padjadjaran, Indonesia, 2020)
Stroke and heart disease belong to atherosclerotic cardiovascular diseases (ASCVD), which is one of the death causes in Indonesia. This study aimed to estimate the risk of atherosclerosis cardiovascular disease in the next 10 years using the Systemic Coronary Risk Estimation (SCORE) method. This research was an observational study with descriptive cross-sectional study design. Respondent data collection was taken prospectively which means directs data was collected through interviews, blood pressure measurement, and peripheral blood sampling. The results showed that respondents who were involved in this study were those with an average age of 49.70 ± 7.1 years. Respondents were more dominated by women (76.1%); BMI of respondents showed in the non-obese group 27.14 ± 4.6 kg/m2; total cholesterol, LDL, TG, and HDL levels respectively had an average of 152.17 ± 39.5 mg/dL; 91.28 ± 40.9 mg/dL; 117.24 ± 96.9 mg/dL; and 30.87 ± 8.8. The number of respondents who smoke was 17.39% and that of those who have undergone physical activity in the form of sports was 60.87%. Based on the results of risk estimation using the SCORE method, it was found that the number of people who were in the low-risk category was 54.35% and the moderate risk category was 45.65%. This study concludes that the risk of ASCVD for the next 10 years in the community is at low and moderate levels. Non-pharmacological treatment is more recommended at this level and statins can be given to individuals if there is no improvement in cholesterol levels.